Histeroskopska resekcija pregrade - vpliv na nosečnost - Ban, Helena (Zdravniški vestnik, 2003)
Background. In women with spontaneous abortions, preterm deliveries or infertility, septate uterus is often detected on transvaginal ultrasound examination. Since 1993 we have used hysteroscopic resection to correct this anomaly. The aim of this study was to evaluate the effect of the arcuate uterus on the course of pregnancy and its outcome, and the effect of hysteroscopic resection of the arcuate uterus on the prognosis of pregnancy. Patients and methods. Retrospectively we analyzed prospectively collected data. Between 15 February 1993 and 31 December 1999 we performed 760 hysteroscopic resections of the septum at the Department of Obstetrics and Gynecology in Ljubljana. We evaluated the course of pregnancy and its outcome only, therefore we enrolled 241 women, who conceived spontaneously before and after operation. Results. In the group of women with arcuate uterus (n =111) there were 244 pregnancies before hysteroscopic resection. 38 (15.6%) ended with a delivery and 202 (82.8%) with a spontaneous abortion. In the group of women with septate uterus (n = 230) there were 269 pregnancies: 42 deliveries (15.6%) and 224 (83.3%) spontaneous abortions. After hysteroscopic resection there were 109 pregnancies in the women with arcuate uterus: 91 (83.5%) deliveries and 16 (14.7%) spontaneous abortions; in the septate uterus group there were 118 pregnancies: 98 (83.2%) deliveries and 16 (13.5%) spontaneous abortions. In both groups there was a significant improvement in the delivery rate (p < 0.00000). Before resection the preterm delivery rates were significantly higher in both groups (arcuate: 50.0%; septate: 35.1%) than after the resection (arcuate: 11.3%; septate 17.7%). Conclusions. The women with either septate or arcuate uterus are at a higher risk for spontaneous abortion and preterm delivery. Hysteroscopic resection significantly decreasesthe risk in both groups of women.
Keywords: Abnormalities; Abortion, Missed; Abortus zgrešeni; ginekologija; Histerosalpingografija; Histeroskopija; Hysterosalpingography; Hysteroscopy; Labor, Premature; Maternica; nepravilnosti; Nosečnost; Nosečnost, komplikacije; Porod prezgodnji; Pregnancy; Pregnancy Complications; Uterus; zdravljenje